Reduced morbidity and mortality of cGVHD in patients who received treatment with mesenchymal stromal cells for steroid-resistant aGVHD: long-term follow-up of a randomized phase 3 trial - Ke Zhao; Ren Lin; Zhiping Fan; Zhen Li; Xiaoyong Chen; Li Xuan; Fen Huang; Na Xu; Xiuli Wu; Shaohua Chen; Jing Sun; Xi Zhang; et al. (Experimental Hematology & Oncology)
Abstract Background Our open-label, multicenter, randomized, phase 3 trial showed that the incidence and severity of chronic graft-versus-host disease (cGVHD) reduced in steroid-resistant acute graft-versus-host disease (aGVHD) patients who underwent mesenchymal stromal cells (MSCs) treatments, but survival benefit was not received. Here, we present a post-hoc analysis of the 5-year follow-up to explore long-term survival and its underlying mechanism. Methods This long-term follow-up trial included steroid-resistant aGVHD patients, who were randomly assigned (1:1) to receive MSCs (MSC group) (1 × 106 cells/kg once weekly for 4 consecutive weeks, 8 doses at most) or without MSCs treatment (control group). For this updated analysis, the 5-year endpoints were cumulative incidence of cGVHD, overall survival, cGVHD-free, relapse-free survival (CRFS), and relapse. To explore the mechanism, We investigated the changes in T, B cells, and signal joint T cell receptor excision DNA circles (sjTRECs). Results Between September 2014 and March 2019, 198 patients were randomly assigned to the MSC group (n = 99) or the control group (n = 99). Extended follow-up showed the lower 5-year cumulative incidence of cGVHD (42.0% [95%CI 32.2–51.5] vs. 67.1% [55.6–76.3]; hazard ratio [HR] 2.19, 95%CI 1.47–3.27; P < 0.001), improved 5-year overall survival (60.4% [50.8–70.0] vs. 41.7% [31.9–51.5]; 0.63, 0.42–0.94; P = 0.023), CRFS (33.9% [24.5–43.3] vs. 20.9% [12.9–28.9]; 0.67, 0.48–0.93; P = 0.017) and no increase on relapse (13.6% [7.6–21.3] vs. 16.0% [9.5–23.9]; 1.24, 0.60–2.56; P = 0.568) for patients in MSC group compared with the control group. Clinical improvement of MSCs was accompanied by significant increases in regulatory T cells, CD4 + CD45RA + CD31 + naïve T, CD19 + CD27 + IgD- memory B cells, and sjTRECs. Conclusions With extended follow-up, MSCs reduced the morbidity of cGVHD in aGVHD patients and improved overall survival and CRFS. Mechanistically, MSCs reduced cGVHD by thymus pathway. Trial registration clinicaltrials.gov identifier: NCT02241018. Registration date: 16 September 2014, https://clinicaltrials.gov/ct2/show/NCT02241018 .